PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI PADA KANTOR KELURAHAN LOA BAKUNG KECAMATAN SUNGAI KUNJANG KOTA SAMARINDA - Fauziah, Fina (PREDIKSI, 2012)
ABSTRACTÂ The purpose of this study was to determine whether the monitoring effect on employee discipline. To get the data the authors conducted research on Kantor Kelurahan Loa Bakung Kecamatan Sungai Kunjang District of Samarinda.The results showed that the control effect on employee discipline at the Kantor Kelurahan Loa Bakung Kecamatan Sungai Kunjang District of Samarinda.Â Hal ini dapat dibuktikan bahwa hasil dari analisis data rs hitung yang diperoleh lebih besar dibanding dengan harga table yaitu 0,770 > 0,456 to significant level 95 % untuk N = 14.Â It can be proven that the results of the analysis of data obtained rs count greater than the price table is 0.770; 0.456 at 95% confidence level for N= 14. Thus, this hypothesis can be accepted that the control effect on labor disciplin to Kantor Kelurahan Loa Bakung Kecamatan Sungai Kunjang District of Samarinda.